PENGARUH SIKAP KERJA, LINGKUNGAN KERJA DAN KETERLIBATAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN DIVISI HR & GA PT ALTRAK 1978 JAKARTA - Cahyo Aldian Rahmatullah (2022)
This research is a quantitative research that has the aim of testing, knowing, and proving the effect of Work Attitude, Work Environment, and Work Engagement on Job Satisfaction. This research was conducted on employees of the HR & GA division of PT Altrak 1978 Jakarta, with a total sample of 50 employees. The analysis technique used in this research is descriptive analysis and inferential analysis which consists of validity test, reliability test, coefficient of determination test, and hypothesis testing using SmartPLS 3.0 tool. The results of this study showed that (1) work attitude had no significant effect on employee job satisfaction in the HR & GA division of PT Altrak 1978 Jakarta, (2) the work environment had a significant effect on employee job satisfaction in the HR & GA division of PT Altrak 1978 Jakarta, (3) Work Engagement has a significant effect on employee job satisfaction in the HR & GA division of PT Altrak 1978 Jakarta, and (4) Work Attitude, Work Environment, and Work Engagement have a significant effect together on job satisfaction in the HR & GA division of PT Altrak 1978 Jakarta.